دراسة تأثير الظروف المناخية على إنتاجية الفستق الحلبي Pistacia Vera في حلـب وإدلـب (Latakia University Journal -Biological Sciences Series, 2018)
وضحت نتائج الدراسة وجود تباين واضح في الظروف المناخية لمنطقتي زراعة الفستق الحلبي   الرئيسية في سورية أدى إلى تفاوت في إنتاجيته حيث  بلغت  6.86 في حلب و 10.35كغ/ شجرة في إدلب ،  مع وجود اتجاه تراجعي للإنتاجية خلال الفترة  (1982- 2002)  مقداره -2.88 كغ/ شجرة في حلب و- 1.18 كغ/ شجرة في إدلب. دلت التراكمات الحرارية للفترة من الإزهار وحتى النضج إلى وجود زيادة واضحة بلغت +173.26 و +339.77 مع تراجع واضح لعدد ساعات البرودة للفترة الشتوية بلغ على التوالي - 218.69 في حلب وفي إدلب -229.53 . أظهرت قيم معامل الارتباط البسيط التأثير الإيجابي القوي لأمطار شهر آذار فقد بلغت قيم (r) +0.88 في حلب و+0.92 في إدلب ، أما التأثير السلبي الأقوى فكان لدرجة الحرارة الصغرى خلال فترة الإزهار وقد بلغ -0.60 في حلب  و-0.59 في إدلب. أخيراً ربطت معادلتا الانحدار المتعدد بين إنتاجية الفستق الحلبي وأهم ثمانية عناصر مناخية مؤثرة خلال المراحل الفينولوجية المختلفة في حلب وإدلب. The result of this study revealed clear variation in the climatological condition between the two regions under study (Aleppo and Idleb). This variation in climatological conditions led to variation in the yield of pistacia vera. The yield of pistachio was 6.86kg/tree (Aleppo) and 10.35kg/tree(Idleb), with a decrease during this period of -2.88 and -1.18 kg/tree/year for Aleppo and Idleb respectively. Thermal accumulation for the period from flowering to maturity showed clear increase (+173.26 and + 339.77), but the number of cool hours during the winter period decreased by -218.69 and -229.53 in Aleppo and Idleb respectively. Simple correlation coefficient values (+0.88 and +0.92) indicated strong positive influence on pistacia vera resulting from the minimum temperature during the flowering period -0.60 and 0.59 for Aleppo and Idleb respectively. Finally, the multi-slope equation related pistachio yield to the eight most important climatological conditions affecting pistacia vera during the phonological stages in Aleppo and Idleb.